Measuring the effects on quality of life and alcohol consumption of a program to reduce binge drinking in Spanish adolescents. (1st December 2019) - Vargas-Martínez, Ana Magdalena; Trapero-Bertran, Marta; Lima-Serrano, Marta; Anokye, Nana; Pokhrel, Subhash; Mora, Toni
Highlights: ALERTA ALCOHOL program was effective to reduce binge drinking (BD). A higher adherence to program increases health-related quality of life (HRQoL). Age, family alcohol consumption and having partner negatively affected the HRQoL. Girls reported lower score in 'pain/discomfort' and 'anxiety/depression.' Abstract: Aim: To present a comparison between the effects on health due to a reduction in binge drinking (BD) and health-related quality of life (HRQoL), as a result of ALERTA ALCOHOL, an intervention aimed at reducing BD in Spanish adolescents. Methods: A two-arm cluster randomized controlled trial was conducted with an intervention and a control group, randomized at the school level, following individuals over four months. The study population consisted of Andalusian adolescents aged 15 to 19 years who were enrolled in urban public high schools (n = 1247). Participants were assigned randomly to receive the intervention. The main outcomes studied were the number of occasions of BD in the last 30 days, which was directly obtained from the answers given by the adolescents, and HRQoL measured with the EQ-5D-5 L questionnaire. The model of estimation was the generalized estimating equations (GEE) approach. Results: The program showed a BD reduction at the 4-month follow-up, although it was not shown to significantly increase the HRQoL in adolescents who reduced the number of occasions of BD and had received the intervention. However, it was shown that those who would predictably reduce the number of occasions of BD controlled by several sociodemographic variables perceived a higher HRQoL, as did those who had a greater adherence to the program. Conclusions: Higher adherence to a web-based computer-tailored intervention to prevent BD in adolescents has a positive effect on decreasing the number of occasions of BD in adolescents as well as on increasing participants' HRQoL, although this second effect is very small, which could be due to the short follow-up time. This fact is quite important and should be assessed extensively to corroborate the results and translate into health policy.